Health profile of foreign workers - lifestyle habits / risk behaviours - Wong, Yut Lin (Faculty of Medicine, University of Malaya, 2002)
The majority of migrant workers studied in this survey were males Muslims from Bangladesh. The mean was 30 and the majority were aged between 21-30 years. Although almost all of them had 7-13 years of schooling, the majority were working in the service industry. More than two thirds of the migrant workers were provided with various forms of housing by their employers. Majority of them stated that they had better amenities, such as piped drinking water and sanitary toilets, in Malaysia compared to those in their home countries. From their reports, it appears that the majority did not engage in risk behaviours such as, smoking, alcohol and drug abuse.